Investigation of the Effects of Buildup Factors on Electromagnetic Radiation Dose - Ayomide Matthew Adefisoye; Steve Idowu; Abdulrasheed Sado (The Journal of Engineering and Exact Sciences)
The buildup factor is an important element in radiation protection and shielding. It is also an essential component of the equation for dose calculation. In this study, dose conversion factors were calculated for outside exposures from gamma-rays. The calculations were established on the point-kernel integration method where two expressions for buildup factor were tested; (a) Taylor’s buildup factor and (b) Linear buildup factor. Dose calculations were performed for the two buildup factors expressions at energy range of 0.01MeV – 10.00MeV. The calculations yielded two results for the Dose conversion factor, which are at variance within the range 0.01-3.00MeV and > 5.00MeV. However, there is apparent agreement between the two results for energy range 3.00-5.00MeV. The result for the Taylor’s build-up factor correlates closely with the earlier results obtained from experimental and theoretical approaches. It has therefore been revealed that the choice of buildup factor used in dose calculation affects the output of the calculation.